Kinship-Based Political Practices in the Government of Muara Opu Village, Muara Batang Toru District - Ardi Rusman; Hasrul (Lembaga Bale Literasi, 2025)
The development of kinship politics in Indonesia in the current era of electoral democracy is indeed a trend that needs to be slowed down even if it is possible to end. This cannot be separated from the many evils and weaknesses of the political order filled by certain kinship and political dynasties, so that criticism, supervision, and the mechanism of checks and balances are difficult to carry out. So far, the existing studies have not paid attention to kinship politics that occur within the scope of village government because they tend to only look at kinship politics in the context of practical politics, namely the election of regional heads. This paper complements the shortcomings of existing studies that do not carefully analyze the practice of kinship politics in village government. In line with that, there are three questions that can be formulated: (1) what is the form of kinship political practice that occurs in Muara Opu Village; (2) what are the factors that support kinship politics in Muara Opu Village, obstacles for female politicians in using the modalities they have to win the 2019 election contest in Padang City; The answers to these two questions provide an in-depth understanding as the basis for formulating policies to prevent the occurrence of kinship politics in Muara Opu Village. The result of this research is that there are forms of kinship politics in Muara Opu Village in the form of non-transparent filling of positions and uneven distribution of social assistance. In addition, the factors that encourage kinship politics are weak leaders and an unclear recruitment system. Finally, the results of this study are the impact of kinship politics such as discriminatory treatment and inhibition of the development process in Muara Opu Village.